Interface bond relaxation on the thermal conductivity of Si/Ge core-shell nanowires - Chen, Weifeng (2016)
The thermal conductivity of Si/Ge core-shell nanowires (CSNWs) is investigated on the basis of atomic-bond-relaxation consideration and continuum mechanics. An analytical model is developed to clarify the interfacebond relaxation of Si/Ge CSNWs. It is found that the thermal conductivity of Si core can be modulated through covering with Geepitaxial layers. The change of thermal conductivity in Si/Ge CSNWs should be attributed to the surface relaxation and interface mismatch between inner Si nanowire and outer Geepitaxial layer. Our results are in well agreement with the experimental measurements and simulations, suggesting that the presented method provides a fundamental insight of the thermal conductivity of CSNWs from the atomistic origin.